2015
DOI: 10.1038/ijo.2015.188
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic stearoyl-CoA desaturase-2 (SCD2) controls whole-body energy expenditure

Abstract: Thus, SCD2 is highly expressed in the hypothalami of rodents and its knockdown reduces body mass due to increased whole-body energy expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
2
13
0
1
Order By: Relevance
“…In addition, the molecular localization of JAZF1 signaling by MBH Ad‐ JAZF1 is another important issue of concern. Similar to previous reports, 58‐60 we demonstrated that the injection of Ad‐ GFP into the MBH resulted in an effect that was anatomically restricted to the hypothalamic region related to energy balance. It should also be noted that in addition to the association between the liver and the brain, changes in food intake, BW, and other metabolic tissues (eg, fat and muscle) can also alter the degree of insulin sensitivity in the entire body and liver.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the molecular localization of JAZF1 signaling by MBH Ad‐ JAZF1 is another important issue of concern. Similar to previous reports, 58‐60 we demonstrated that the injection of Ad‐ GFP into the MBH resulted in an effect that was anatomically restricted to the hypothalamic region related to energy balance. It should also be noted that in addition to the association between the liver and the brain, changes in food intake, BW, and other metabolic tissues (eg, fat and muscle) can also alter the degree of insulin sensitivity in the entire body and liver.…”
Section: Discussionsupporting
confidence: 90%
“…Scd2 is a crucial enzyme in the synthesis of monounsaturated fatty acids which are required for maintaining a normal epidermal permeability barrier function, and are components of triglycerides (Miyazaki et al, 2005). Alterations in Scd2 levels may affect lipid content in non-hepatic organs (de Moura et al, 2016) where level and type of lipid is critical to function. Elovl-6 is one of six mammalian enzymes responsible for fatty acid elongation beyond 16 carbons to produce very long chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The control group (MO) average on each treatment day (day 2, 4 or 10) was used to calibrate all groups. PCR efficiency was calculated prior to the experiments, and the 2^-DDCT method was used to calculate gene expression [20].…”
Section: Methodsmentioning
confidence: 99%